2018
DOI: 10.2991/cmsa-18.2018.51
|View full text |Cite
|
Sign up to set email alerts
|

Teeth Category Classification via Hu Moment Invariant and Extreme Learning Machine

Abstract: Abstract-To improve the computer-assisted diagnosis and decision in dentistry, we tested a new method combining Hu moment invariant (HMI) method and extreme learning machine (ELM) to implement the teeth classification in cross-section image of Cone Beam Computed Tomography (CBCT). 160 images were analyzed and 4 categories were recognized. The results showed the sensitivities of incisors, canine, premolar, and molars were 78.25± 6.02%, 78.00± 5.99%, 79.25± 7.91%, and 78.75± 5.17%, better than ANN statistical-si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…ELM generates prediction output with a 0.0426 low error rate. Combining the Hu moment invariant (HMI) method with ELM, [ 47 ] devised and implemented a unique classification technique for CBCT images of teeth. The results showed that the devised methodology is better compared to a statistically significant ANN.…”
Section: Resultsmentioning
confidence: 99%
“…ELM generates prediction output with a 0.0426 low error rate. Combining the Hu moment invariant (HMI) method with ELM, [ 47 ] devised and implemented a unique classification technique for CBCT images of teeth. The results showed that the devised methodology is better compared to a statistically significant ANN.…”
Section: Resultsmentioning
confidence: 99%